Rancang Bangun dan Simulasi 3D Printer Model Cartesian Berbasis Fused Deposition Modelling - Romario A Wicaksono; Eddy Kurniawan; M Khalid Syafrianto; Ramadhani Fadelandro Suratman; M Ridho Sofyandi (Jurnal Engine: Energi, Manufaktur, dan Material, 2021)
The process of designing and manufacturing a Cartesian 3D printer model based on Fused Deposition Modelling (FDM) is carried out to produce a 3D printer machine that can perform the printing process accurately and quickly. In this research, the process is divided into three stages, namely designing using Computer-Aided Design (CAD) software, printing and assembling components of a 3D printer machine, and analysing the mechanical structure of a 3D printer machine. This 3D printer is designed to carry out the printing process with an area of 180x180x150 mm. Some components of 3D printing machines use Polylactic Acid (PLA). The simulation results based on the Finite Element Method show that the 3D printer engine is feasible to produce printing with a mass of 40% of the maximum possible load.